2023
DOI: 10.3390/antibiotics12020395
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Drug Resistance Pattern of Uropathogens in Pediatric Patients in Pakistani Population

Abstract: The common prevalent diseases in the age of 0 to 6 are related to urinary tract infections. If not properly diagnosed, they will lead to urological and nephrological complications. Uropathogens are developing resistance against most drugs and are harder to treat. A study was done on the inpatients and outpatients of the two hospitals located in Lahore. A total of 39,750 samples that were both male and female were collected. Escherichia and Klebsiella were found in 234 samples based on biochemical characterizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
2
2
1
Order By: Relevance
“…The resistance pattern of third generation cephalosporins was higher than those of meropenem and imipenem. These results are consistent with the previous studies [23,24]. The resistance patterns of both groups (ward and OPD) of the isolates showed higher resistance to penicillin, cephalosporins, and quinolones.…”
Section: Discussionsupporting
confidence: 93%
“…The resistance pattern of third generation cephalosporins was higher than those of meropenem and imipenem. These results are consistent with the previous studies [23,24]. The resistance patterns of both groups (ward and OPD) of the isolates showed higher resistance to penicillin, cephalosporins, and quinolones.…”
Section: Discussionsupporting
confidence: 93%
“…Sensitivity to trimethoprim-sulphmethoxazole in our study was 19% only, while in previous studies it was 97 % 16 , 70% 19 , 63% 9 , 50% 2 , 42% 3 , 39% 13 , 26% 7 , and only 6%. 10 Sensitivity to cephalosporin in our study was only 8% which is quiet alarming situation for our geographic area because in previous studies sensitivity to cephalosporins was quite good, i.e., it was 85% to cefoxitin, 82% to cefotaxime, and 75% to ceftazidime in one study 3 while in other studies it was 93 % to ceftriaxone 16 , 74% to cefotaxime 9 and 19.8% to cefixime. 1 Similarly studies conducted in Pakistan previously which shows sensitivity of 32.3%, 39%, 21.3% and only 10% to ceftriaxone 18,1,19,10 whereas sensitivity to cefotaxime 23.8% and 22.5%.…”
Section: Discussioncontrasting
confidence: 55%
“…18 In our study E. coli was 94% sensitive to amikacin whereas in other studies sensitivity to amikacin were 89.5% 19 , 87% 7 , 81%, 2 95.5% 9 , 40.4%, 1 51% 18 , and 63%. 10 In our study sensitivity to cefoperazonesulbactam, piperacillin-tazobactam and Nitrofurantoin was >80%. Other studies in the past also shows the similar results for nitrofurantoin 98%, 85.3%, 82%, 97%, 88%, 83%, and 82%.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…This pattern is in line with a number of research studies conducted in Pakistan in the past decade that showed Enterobacterales’ increasing resistance to the cephalosporin and penicillin class of antibiotics. 14 , 23 - 25 …”
Section: Discissionmentioning
confidence: 99%